Internet of Things in the Healthcare System: A Study - Padashetti, Mallikarjun S; Meharunnisa, S. P. (Journal of ISMAC, 2022)
Today’s health care is increasingly focused on technology. Unexpected deaths among humans are a problem that arises from delayed medical attention. The development of a body health monitoring system is therefore necessary. The Internet of Things (IoT) enables the integration of numerous devices capable of connecting to the internet, providing information on the state of a patient’s health and providing information in real time to doctors who can help. The term "Internet of Things" (IoT) refers to a system or methodology that enables physical objects to connect and communicate with one another through networking technology. The in-depth analysis of developments in IoT-based healthcare methods is presented in this paper. It also categorises a prevailing IoT-based healthcare net and provides a summary of all prospective systems. In this context, study of IoT health care protocols offers a thorough overview of the topic. A thorough survey of IoT healthcare services and applications is also launched. IoT device data can assist medical professionals in choosing the most effective course of therapy for patients and achieving desired results. For achieving requirements like Data and device security, encompassing the confidentiality and integrity of data as well as the authentication of devices, IoT has been established in healthcare system.